Consumer Rights & Customer Loyalty of Online Food Delivery Services Among Consumers in Sarawak - Fadilah, Siali; Mahani Mohammad, Abdu Shakur; Muhammad Hafiz, Mohd Shukri (International Journal of Business and Society, 2024)
Online Food Delivery Services (OFDS) is gaining popularity as one e-commerce platform. This paper aims to empirically evaluate consumers' awareness of their rights using OFDS services, determine whether their experience exercising consumer rights when using OFDS, and examine whether their experience exercising these rights affects their loyalty to their preferred OFDS. The selected consumer rights for this investigation include Rights to Basic Needs, Rights to Information, Rights to Choose, Rights to Safety and Rights to Redress. Employing a quantitative approach, this study surveyed questionnaire distribution across four main divisions in Sarawak: Kuching, Samarahan, Sibu and Miri. The data was analysed using multiple regression analysis techniques. The results indicate that Consumer Rights to Basic Needs, Rights to Information, and Rights to Choose significantly influence loyalty. Both the Rights to Safety and Rights to Redress positively affect loyalty, but their influence is not statistically significant. Furthermore, Mann-Whitey U Test was employed to compare the means of two prominent OFDS platforms preferred by the respondents, namely GrabFood and Foodpanda. The findings suggest no significant difference between the sample means for all the variables used in this study. This study provides a fresh insight into the consumer rights and protection of OFDS from both marketing and consumerism perspectives.